The mechanisms of treatment resistance in psychiatry in the aspects of pharmacodynamics of psychotropic drugs - V. L. Kozlovskii (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Treatment resistance is a persistent neurochemical condition characterized by the presence of the «hybrid», combined pathological and drug metabolism. The difficulties in management and prevention of resistance relate to the lack of understanding of neurochemical changes occurring in the neuronal networks during development of the higher mental functions. Within the concept of the species-preserving behavior development neurochemically associated with the activity of monoaminergic systems in determined pathways and local neuronal networks with the co-transimitterts’ modulation of functions, pharmacodynamics of psychotropic drugs are discussed. The ability of psychotropic drugs to alter the mental state is determined by rapid and slow effects associated with the changes in monoaminergic processes at all levels of mediation (the synapses, the activity of neurons, local neuronal networks). It is emphasized that divergent neurochemical changes and the heterogeneity of the resistance development after treatment with agonists (antidepressants, anxiolytics, etc.) and antagonists (antipsychotics) determine the multiplicity of pharmacological approaches to the patients’ therapy. Accordingly, methodological aspects of resistance management by so-called «opposite therapy», «sensitization» and combination treatment strategies depending on the medications pharmacodynamics are considered.